Efficiency of the Japanese affiliates: Regional economy perspectives - Yong, C.C.; Chan, S.G. (Universiti Putra Malaysia, 2017)
Japanese merger and acquisitions strategy to leverage country's cheap labour and establish long-term competitive advantage has been challenged by today's world economy that performed below the expected growth. This study explores the efficiency of the Japanese affiliates in the regions of North America, European Union, Newly Industrialized Economies (NIEs), ASEAN4 and China for manufacturing sub-sector from 1997 to 2012 that believe could help Japan to regain her competitiveness. Results found that the Japanese affiliates in North America and Europe are relatively efficient as compared to the rest of the regions. The efficiency for iron and steel industry is relatively higher as compared to other manufacturing industries in ASEAN4, NIEs and China. The efficiency for electrical machinery in Europe and transportation, electrical machinery and chemical in North America industry are relatively higher as compared to other manufacturing industries.